Hubungan Antara Dukungan Organisasi (Organizational Support) Terhadap Kepuasan Kerja Pada Guru TK Di Padang Lawas Utara - Afriani Srg, Yetty; Irna Aviani, Yolivia (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
Job satisfaction is a psychological aspect that reflects a person's feelings towards his or her job, feeling satisfied with the suitability of abilities, skills and expectations with the job at hand. Teachers who feel that their salary is not appropriate can form a form of financial compensation received by teachers at a certain time for their contribution to the principles of fairness and justice. One of the variables related to job satisfaction is organizational support, where organizational support is a form of view of employees regarding the extent to which the workplace organization cares about welfare. So this research aims to look at the relationship between perceptions of organizational support and job satisfaction among kindergarten teachers in Padang lawas utara. The subjects of this research were 50 respondents who were kindergarten teachers in North Padang Lawas utara through quota sampling. The data analysis used was product moment correlation. The results of this research found that there was a relationship between perceptions of organizational support and job satisfaction among kindergarten teachers in North Padang Lawas utara. Obtained from a correlation value of -0.453 which shows that the correlation between the two variables is negative. This means that the higher a person's perception of organizational support, the lower the job satisfaction they experience and vice versa.